Answer:
81 9^2
Step-by-step explanation:
3•3= 9
3•3=9
9•9=81
and 9•9=81
Answer:
C. 8x - 16
D.
+ 6x + 8
A. 2 (x + 3)
B. 7(2 - x)
C. -8x
D. 7x
Step-by-step explanation:
c.
To solve this problem, first, one must distribute, multiply every term inside the parenthesis by the term outside,
2(4x - 8)
=(2)(4x) + (2)(-8)
= 8x - 16
d.
To solve this problem, distribute, multiply every term inside one parenthesis by every term in the other, the combine like terms,
(x + 4)(x + 2)
= (x)(x) + (4)(x) + (2)(x) + (4)(2)
=
+ 4x + 2x + 8
=
+ 6x + 8
a.
Factor, write the given expression as the product of two expressions. Take out a common factor that both terms have,
2x + 6
= 2(x + 3)
b.
Factor this expression, take out a common factor, and rewrite the expression as the product of two other expressions,
14 - 7x
7(2 - x)
c.
Combine like terms,
2x - 10x
= -8x
d.
Combine like terms to solve this problem
3x + 4x
= 7x
Answer:
-2(x^2 - x - 1).
Step-by-step explanation:
3x - 2x^2 - x + 2
= 2x - 2x^2 + 2
= -2(x^2 - x - 1)
Answer:
V= 628.32
Step-by-step explanation:
Answer:
D[3, 3], C[1, 4], B[0, 1], A[4, -1]
Step-by-step explanation:
Whenever you are doing a 90° clockwise rotation ABOUT THE ORIGIN, it is in the form of [<em>y</em><em>,</em><em> </em><em>-</em><em>x</em>], meaning you take the <em>y</em><em> </em>and make it your <em>x</em><em>,</em><em> </em>then take your original <em>x</em><em> </em>and put its OPPOSITE.
90° counterclockwise rotation → [<em>-y, x</em>]
90° clockwise rotation → [<em>y, -x</em>]
I hope this helps, and as always, I am joyous to assist anyone at any time.